2015
DOI: 10.1093/europace/euv210
|View full text |Cite
|
Sign up to set email alerts
|

Red cell distribution width as a novel predictor for clinical outcomes in patients with paroxysmal atrial fibrillation

Abstract: RDW can be a new, useful, novel predictor of clinical and safety outcomes in patients with paroxysmal AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…There are multiple other factors, such as vascular damage caused by stent placement, local and systemic inflammatory responses induced by stent implantation and of coronary lesion severity, that may also affect stent restenosis. The red cell distribution width (RDW), which is commonly used to evaluate anaemia, has emerged as a new cardiovascular prognostic marker, and increased RDW values have been shown in patients with heart failure,8 coronary events,9 10 paroxysmal atrial fibrillation11 and end-organ damage with systolic-diastolic hypertension 12. In this retrospective study, we analysed the RDW, clinical features, serological indexes and coronary angiography results to determine the risk factors for ISR and provided a theoretical basis for preventive stent restenosis treatment after PCI.…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple other factors, such as vascular damage caused by stent placement, local and systemic inflammatory responses induced by stent implantation and of coronary lesion severity, that may also affect stent restenosis. The red cell distribution width (RDW), which is commonly used to evaluate anaemia, has emerged as a new cardiovascular prognostic marker, and increased RDW values have been shown in patients with heart failure,8 coronary events,9 10 paroxysmal atrial fibrillation11 and end-organ damage with systolic-diastolic hypertension 12. In this retrospective study, we analysed the RDW, clinical features, serological indexes and coronary angiography results to determine the risk factors for ISR and provided a theoretical basis for preventive stent restenosis treatment after PCI.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a series of clinical experiments have revealed that an increased RDW is an independent predictive factor of poor prognosis for cardiovascular diseases, such as cardiac failure, coronary heart disease and AF [21,22,23,24,25,26]. Kurt et al [14] discovered that high RDW is an independent predictive factor for a high CHA 2 DS 2 -VASc score, while Lee et al [13] found that the CHA 2 DS 2 -VASc score and the occurrence rate of ischemic stroke increase with an increase in RDW. It can be seen that high RDW is associated with an increased risk of AF embolism.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there has been little relevant research on RDW and the risk of bleeding for AF patients when taking anticoagulants. Though Lee et al [13] indicated in their research that the occurrence rate of bleeding events increased with the increase in RDW, they did not mention the specific anticoagulant used. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the management of AF is very important, especially in terms of preventing thromboembolic events. Recently, studies have reported that a high red blood cell distribution width (RDW) is associated with a poor prognosis and bleeding events in patients with AF [3,4]. …”
mentioning
confidence: 99%